CHEMICAL COMPOSITION OF THE ATMOSPHERES OF THREE GIANTS IN HYADES - Mishenina, T. V.; Komarov, N. S.; Kantsen, L. E. (Одеські астрономічні публікації, 2017)
The abundances and physical conditions in the atmospheres of three Hyades giants have been investigated by using the high-dispersion (5.6 A/mm) spectra obtained at the 6-m telescope of the Special Astrophysical Observatory. The empirical analysis of the deviations from LTE for the Fe lines with the low and high excitation potentials showed the slight differences within the limits of the determination errors. The abundances of 22 chemical elements the atmospheres of the K-giants derived by the method of the model atmospheres differ from the solar one. Underabundance of O and overabundance of Na of about 0.5 dex and of elements after Y of about 0.2 dex are established.